The impact of leadership development on student outcomes within private schooling; a case study of a high school in the Midlands, Kwazulu-Natal - Jones, Robin (The IIE, 2018)
Leadership in education matters only if it contributes to better educational outcomes for students. The phrase ‘student outcomes’ is used not just to the shorter-term measures of academic achievement that tend to dominate research in this area, but to the entire range of outcomes of schooling that are of concern to students and the public. Since education is largely appreciated for its instrumental value, people care far more about longer-term indicators of education success, such as high school graduation, repetition in grade or course failure, suspension and expulsion, and student engagement. The purpose of this research study is to reveal the importance of leadership development and addressing developmental needs and the impact it may have on student outcomes. A greater focus on schooling and student outcomes have made the role of school leaders even more essential. A series of interviews were conducted at a private school in the Midlands, Kwazulu-Natal. These interviews were conducted via a snowball sampling technique and were used to determine themes. Saturation was reached, and themes were then further investigated. Are schools providing a platform for growth for students, as well as educators and does leadership development impact on student outcomes?
Keywords: private schooling; leadership development; student outcomes; developmental needs; leadership in education